Economic analysis of scenarios for the sustainability of extensive livestock farming in Spain under the CAP - Franco, Juan Agustín; Gaspar, Paula; Mesias, Francisco Javier (Ecological Economics, 2012)
This paper proposes a change in the conditions of cross-compliance of CAP payments. Speciﬁcally, the eligibility criterion considered is compliance with minimal requirements of long-term economic and agroenvironmental sustainability. To this end, 69 range farms were surveyed in Extremadura (SW Spain). In these farms, sustainability was studied using the MESMIS framework. MESMIS is based on the evaluation of basic attributes of sustainability (adaptability, self-reliance, equity, stability, and productivity) formed from different indicators. The original indicators are then synthesized by means of qualitative, quantitative, or mixed techniques into a single value measuring the sustainability of the system (sustainability index). Alternative scenarios were then deﬁned in which the perception of CAP subsidies was to a greater or lesser extent linked to levels of sustainability. For each of these scenarios, the economic indicators of the farms were compared with those of the baseline (present) situation. The analysis was completed using a logistic model classiﬁcation to study the relationship between the maximum levels attainable by the economic indicators in terms of the sustainability indices. The results showed that including sustainability as a condition for receiving aid under the CAP can contribute to improving the economic results of traditional extensive farms.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: common agricultural policy; Cross-compliance; Dehesa; Extremadura; Logistic models; Sustainability

Influence of Climate on Radial Growth of Holm Oaks (Quercus Ilex Subsp. Ballota Desf) from SW Spain - Patón, Daniel; García-Herrera, Ricardo; Cuenca, Javier; Galavis, Mamen; Roig, Fidel (Geochronometria, 2009)
A total of 47 trunk sections from Holm Oak (Quercus ilex subsp. ballota Desf) trees growing at two different sites at the Extremadura region (SW Spain) were considered in the computation of a regional tree-ring chronology useful to interpret the tree-ring/Mediterranean climate relationships. This is the first dendroclimatological research of Holm Oaks conducted to reveal its potential use as a climatic proxy. The obtained tree-ring chronologies were compared with climatic parameters based on monthly, seasonal and annual rainfall, and monthly maximum, minimum and average temperature. The best correlations were obtained with maximum temperatures during the period between previous winter and early spring. Influence of rainfall was less relevant. Growth of this species indicates a typical bimodal (spring and autumn) strategy that avoids low winter temperatures and summer drought. Despite some technical difficulties recognizing tree rings in Holm Oaks, its good sensitivity to climate variability and its wide distribution and longevity (~800 years), allow us to consider this species as a good candidate for temperature reconstructions in the Mediterranean Basin.
Keywords: climatic change; Dendrochronology; dendroclimatology; Extremadura; maximum temperature; Quercus ilex; Spain; tree rings

Influence of Climate on Radial Growth of Holm Oaks (Quercus Ilex Subsp. Ballota Desf) from SW Spain - Patón, Daniel; García-Herrera, Ricardo; Cuenca, Javier; Galavis, Mamen; Roig, Fidel (Geochronometria, 2009)
A total of 47 trunk sections from Holm Oak (Quercus ilex subsp. ballota Desf) trees growing at two different sites at the Extremadura region (SW Spain) were considered in the computation of a regional tree-ring chronology useful to interpret the tree-ring/Mediterranean climate relationships. This is the first dendroclimatological research of Holm Oaks conducted to reveal its potential use as a climatic proxy. The obtained tree-ring chronologies were compared with climatic parameters based on monthly, seasonal and annual rainfall, and monthly maximum, minimum and average temperature. The best correlations were obtained with maximum temperatures during the period between previous winter and early spring. Influence of rainfall was less relevant. Growth of this species indicates a typical bimodal (spring and autumn) strategy that avoids low winter temperatures and summer drought. Despite some technical difficulties recognizing tree rings in Holm Oaks, its good sensitivity to climate variability and its wide distribution and longevity (~800 years), allow us to consider this species as a good candidate for temperature reconstructions in the Mediterranean Basin.
Keywords: climatic change; Dendrochronology; dendroclimatology; Extremadura; maximum temperature; Quercus ilex; Spain; tree rings

Ascertaining Landscape Perceptions and Preferences with Pair-wise Photographs: Planning rural tourism in Extremadura, Spain - García Pérez, Joséd (Landscape Research, 2002)
Making use of available resources in the most efficient way is a fundamental principle of all development strategies. Landscapes are an abundant natural resource and form an important basis for the tourism industry. The case of rural Extremadura is considered for its potentially important landscape and growing rural tourist sector. A method of landscape analysis based on pair-wise comparison of photographs is used to ascertain the landscape preferences for rambling of tourists in rural areas. Their preferences are analysed according to personal characteristics and holiday activities. It is concluded that the identification of preferences can be of considerable value in the planning of ramblers' routes for specific social groups.
doi: 10.1080/01426390220149539doi: 10.1080/01426390220149539The following values have no corresponding Zotero field: publisher: Routledge
Keywords: Extremadura; landscape assessment; pair-wise analysis; planning; ramblers; tourism

Ascertaining Landscape Perceptions and Preferences with Pair-wise Photographs: Planning rural tourism in Extremadura, Spain - García Pérez, Joséd (Landscape Research, 2002)
Making use of available resources in the most efficient way is a fundamental principle of all development strategies. Landscapes are an abundant natural resource and form an important basis for the tourism industry. The case of rural Extremadura is considered for its potentially important landscape and growing rural tourist sector. A method of landscape analysis based on pair-wise comparison of photographs is used to ascertain the landscape preferences for rambling of tourists in rural areas. Their preferences are analysed according to personal characteristics and holiday activities. It is concluded that the identification of preferences can be of considerable value in the planning of ramblers' routes for specific social groups.
doi: 10.1080/01426390220149539
Keywords: Extremadura; landscape assessment; pair-wise analysis; planning; ramblers; tourism

El ciclo de biomasa en bosques de frondosas del sur de extremadura. variabilidad espacial del desfronde - TORRES, E; CUEVAS, S; VÁZQUEZ, F Ma; SUÁREZ, Ma A (II Congreso Forestal Español, 1997)
The knowledge of the biomass and nutrients cycle is very important for a suitable forest management. In this paper, four broadleaved species litterfall, during november 1996, is studied in Extremadura (Spain): Castanea sativa Miller, Quercus pyrenaica Willd, Q. rotundifolia Lam and Q. suber L. Litterfall is compared in sorne forests with different maturity. Also, orientation, position and individual tree factors influence is analysed
Keywords: Castanea sativa; Extremadura; litterfall; Quercus pyrenaica; Quercus rotundifolia; Quercus suber

FORESTACIÓN CON CUATRO ESPECIES (Quercus coccifera L., Q.faginea Lam., Q. rotundifolia y Q. suber L.) DE FRONDOSAS EN EXTREMADURA P.M. - Vázquez, F M; Suárez, M A; TORRES, E; CUEVAS, S (II Congreso Forestal Español, 1997)
The principal species of interest in order to form forests of mediterranean type (not of riverside) in the South half of the Iberian Peninsula are the genus Quercus L ones. In this work the outputs contrasted of development are introduced, 1 root and systems of protection utilized in a mixed afforestation with four species of the cited genus (Q. coccifera L., Q. faginea Lam., Q. rotundifolia Lam., Q. suber L.), in Extremadura (Spain). The analysis of the data offers different strategies in sylviculture for the forest recuperation of the zone in function of the species that utilize
Keywords: Afforestation; coccifera; Extremadura; faginea; Quercus; rotundifolia; suber; sylvicuIture

El paisaje vegetal de Extremadura, España - Ladero, Miguel (Giornale botanico italiano, 1996)
Abstract The landscape vegetation of Extremadura, Spain. - The main goal of this work is to gain insight into the landscape of region of Extremadura, located in the suothwest quadrant of the Iberian Peninsula. Owing to ecological factors such as temperature, rainfall and soil types, the predominant landscape of the territory is formed by Mediterranean clymatophylous series, whose main emplacements vary a function of the bioclimatic floor. Thus, the mesomediterranean feactures the holm oak (Quercus rotundifolia) and the cork oak (Quercus suber); the supramediterranean, the oak (Quercus pyrenaica), and the oromediterranean, formations of genista (Cytisus oromediterraneus, Echinopartum barnadesii, Genista cinerea subsp. cinerascens).Edaphohygrophylous series are represented by stands of alder (Alnus glutinosa), ash (Fraxinus angustifolia), willow (Salix sp. pl.), box-leafed broom (Securinega tinctoria) and oleander (Nerium oleander). In order to complete our knowledge of this landscape, of special relevance is the single-stratum vegetation colonizing biotopes such as cliffs and gravel pits, wich serve as a refuge to most of the endemic vegetation of Extremadura. On the quartzite rocks crowning the Silurian series, one finds as permanent communities the heliophobic fissuricolous communities belonging to the association Asplenio billotii-Cheianthetum hispanicae the heliophylous association of Diantho lusitani-Jasionetum tomentosi and, at the base of rock formations and isolated bocks the saxicolous communities of Digitali thapsi-Dianthetum lusitani and Phagnalo saxatilis-Rumicetum indurati. These biotopes have an endemic arbustive vegetation definided by Adenocarpetum argyrophylli.
doi: 10.1080/11263509609439514
Keywords: Extremadura; Geosynphytosociology; Iberian peninsula (citation)